Parallel agent-based demographic simulation : application on population forecast of Singapore - Yang, Zihe (2016)
Demographic simulation studies the dynamic population structure of a city or a country. Traditional demography simulation tools focus on population events (e.g. ageing, marriage, fertility and mortality), using population aggregations and stochastic transitions. In this project, we will develop an agent-based demographic simulation tool, which simulates the behaviors of individuals and studies the interactions with each other. Besides the population events, it is can also trace the location (e.g., Urban Planning Area) for individual people. In order to simulate millions of people, the agent-based demographic simulation is usually time-consuming. To solve the problem, we have investigated how to run the large-scale simulation in an efficient and parallel manner by using a group of computers.